Impact of iron chelation with deferasirox on telomere length and oxidative stress in hemodialysis patients: A randomized study - Blanca Olivia Murillo Ortiz; Joel Ramírez Emiliano; Marcos Javier Romero Vázquez; Lauro Fabián Amador Medina; Sandra Martínez Garza; Edna Montserrat Ramos Rodríguez (Nefrología (English Edition))
Background: Recent studies have demonstrated the effectiveness, safety, and tolerability of deferasirox in patients in peritoneal dialysis, however, its effect has not been studied in patients undergoing hemodialysis. Objective: To investigate the impact of iron chelation on telomere length, oxidative stress, and ferritin levels in patients undergoing hemodialysis. Methods: This is an open-label study, with a control group of patients undergoing hemodialysis, who will receive treatment with deferasirox 15 mg/kg/day for 6 months for iron chelation. Telomere length was measured using real-time PCR. Serum ferritin levels and oxidation markers were evaluated. To evaluate the pharmacokinetics and safety of deferasirox, plasma concentrations were analyzed by HPLC. Results: Fifty-four patients were included to receive deferasirox, and a control group of 50 patients. Significant differences were observed in serum ferritin levels (p < 0.0001), TBARS (thiobarbituric acid reactive substances) (p < 0.01). Telomere length had a significant increase after chelation (p < 0.001). The serum deferasirox concentration at zero time at 48 h was maintained within a range of 2.67–23.78 mmol/L. Conclusions: Our results demonstrate that iron chelation in hemodialysis patients significantly reduces ferritin and TBARS, resulting in an increase in telomere length. Deferasirox proves to be beneficial for patients with iron overload undergoing hemodialysis. Resumen: Antecedentes: Estudios recientes han demostrado la eficacia, seguridad y tolerabilidad del deferasirox en pacientes en diálisis peritoneal, sin embargo, su efecto no ha sido estudiado en pacientes sometidos a hemodiálisis. Objetivo: Investigar el impacto de la quelación del hierro sobre la longitud de los telómeros, el estrés oxidativo y los niveles de ferritina en pacientes sometidos a hemodiálisis. Método: Se trata de un estudio abierto, con un grupo control de pacientes en hemodiálisis, que recibieron tratamiento con deferasirox 15 mg/kg/día durante 6 meses para la quelación del hierro. La longitud de los telómeros se midió mediante PCR en tiempo real. Se evaluaron los niveles séricos de ferritina y los marcadores de oxidación. Para evaluar la farmacocinética y la seguridad del deferasirox, se analizaron las concentraciones plasmáticas mediante HPLC. Resultados: Se incluyeron 54 pacientes para recibir deferasirox, y un grupo control de 50 pacientes. Se observaron diferencias significativas en los niveles séricos de ferritina (p < 0,0001), TBARS (sustancias reactivas al ácido tiobarbitúrico) (p < 0,01). La longitud de los telómeros aumentó significativamente tras la quelación (p < 0,001). La concentración sérica de deferasirox a tiempo cero a las 48 h se mantuvo dentro de un rango de 2,67 a 23,78 mmol/L. Conclusiones: Nuestros resultados demuestran que la quelación del hierro en pacientes en hemodiálisis reduce significativamente la ferritina y el TBARS, lo que se traduce en un aumento de la longitud de los telómeros. El deferasirox demuestra ser beneficioso para los pacientes con sobrecarga de hierro sometidos a hemodiálisis.